Elucidation of key factors of water-resistance of Li-rich solid-solution layered oxide cathode materials applicable to a water-based cathode preparation process for Li-ion battery. (1st September 2018) - Nomura, Fumihiro; Liu, Yubin; Tanabe, Toyokazu; Gunji, Takao; Tsuda, Takashi; Ugawa, Shinsaku; Lee, Hojin; Ohsaka, Takeo; Matsumoto, Futoshi
Abstract: In order to show the best composition which gives water-resistance to Li-rich solid-solution layered oxide cathode materials for a water-based cathode preparation process, the water resistance of LLOs composed of x Li2 MnO3 ― y LiNi1/2 Mn1/2 O2 —(1- x - y )LiNi1/3 Co1/3 Mn1/3 O2 was examined by comparing the charge/discharge cycle results obtained with the cathodes prepared with organic solvent-based and water-based binders. The composition area where the percentage content of Li2 MnO3 is 70–75% was found to show both high charge/discharge capability and water resistance. In addition, by analyzing why this composition of Li2 MnO3 exhibits high water resistance, it has become apparent that the oxidation states of Mn ions and existence of Co ions on the surface of LLOs are the key factors in inhibiting the dissolution of Mn and Ni ions from the LLO surfaces, and finally leading to their high water resistance. Graphical abstract: Image 1 Highlights: A structural-graded Zr50 Ti5 Cu27 Ni10 Al8 amorphous alloy was successfully fabricated. Processing parameters are optimized by using the finite-element method analysis. The gradual strengthen is ascribed to the dispersion of primary hard CuZr2 phase.